2006
DOI: 10.14310/horm.2002.11177
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance, growth factors and cytokine levels in overweight women with breast cancer before and after chemotherapy

Abstract: Post-glucose load insulin values significantly decrease after chemotherapy. There is a positive relationship between BMI and post-glucose load insulin before and after chemotherapy. The contribution of the reduction in insulin, a known growth factor, to the outcome of chemotherapy in these patients remains speculative at present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
(31 reference statements)
3
20
0
1
Order By: Relevance
“…Others have found that in patients with head and neck tumours, FGF-2 and VEGF decrease after radiotherapy, which has an impact on response and progression-free survival [11,12]. VEGF also declined in patients undergoing chemotherapy for advanced breast cancer, in whom the better the response, the greater the drop recorded [13]. Similar results were observed in patients receiving highdose chemotherapy for acute myeloid leukaemia, in whom serum levels of angiogenin and FGF-2 decreased with response [14].…”
Section: Discussionmentioning
confidence: 61%
“…Others have found that in patients with head and neck tumours, FGF-2 and VEGF decrease after radiotherapy, which has an impact on response and progression-free survival [11,12]. VEGF also declined in patients undergoing chemotherapy for advanced breast cancer, in whom the better the response, the greater the drop recorded [13]. Similar results were observed in patients receiving highdose chemotherapy for acute myeloid leukaemia, in whom serum levels of angiogenin and FGF-2 decreased with response [14].…”
Section: Discussionmentioning
confidence: 61%
“…In other words, cancer patients demand more glucose but do not make good use of it, reflecting hypoglycemia [60,61] or hyperglycemia [23,25,33,34], and inducing malnutrition which can lead to death. Moreover, after chemotherapy, glycemia levels may increase [23,25] with a corresponding reduction in insulin [26]. Furthermore, ectopic hormone [27,28], such as adrenal corticosteroid also can elevate plasma glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there are several plausible explanations for the mechanisms by which GMDs develop in cancer patients, including drugs for chemotherapy [23][24][25][26], ectopic hormone [27,28], and destruction of cancer cells or cytokine [28]. However, the prevalent characteristics of GMDs in cancer patients are still unclear, and the disparities of GMDs among different types of cancers are also unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have investigated the parameters of redox and metabolic changes in patients with breast cancer after chemotherapy infusion [15,16] and no differential evaluations regarding cancer disease or treatment-derived alterations have been considered. The scientific literature is controversial regarding the oxidative parameters of patients with breast cancer, who are undergoing chemotherapy.…”
Section: Introductionmentioning
confidence: 99%